Algoritmi za pogajalsko mizo - Franca, Valentina (Delavci in delodajalci, 2026)
The article examines the inclusion of artificial intelligence and algorithmic management in Slovenian collective agreements and situates it within a comparative perspective of more advanced European practices. The analysis shows that this area in Slovenia remains largely normatively unregulated, creating a regulatory gap and reinforcing power asymmetries in the workplace. The article therefore argues for a more proactive and systematic integration of these issues into social dialogue and collective bargaining, drawing on comparative experiences from more advanced European regulatory approaches.
Keywords: algoritemsko upravljanje; algorithmic management; artificial intelligence; collective bargaining; delodajalska združenja; employers’ associations; kolektivna pogajanja; sindikati; social dialogue; socialni dialog; trade unions; umetna inteligenca